Correlation of Left Ventricular Diastolic Dysfunction with Glycemic Parameters in Type 2 Diabetes Mellitus - Revathy. E; K. Suresh, Sheik Anwar Hussain; Baskaran Sreenivasan (The Bioscan, 2025)
Type 2 Diabetes Mellitus (T2DM) is a progressive metabolic condition that contributes significantly to systemic complications, particularly those affecting the cardiovascular system. Diastolic dysfunction, an early manifestation of diabetic heart disease, often develops even in the absence of hypertension or coronary artery disease. This study investigates the frequency of left ventricular diastolic dysfunction (LVDD) in patients with T2DM and explores its association with various glycaemic markers. A hospital-based observational study was conducted over a 12-month period at a tertiary care center in Puducherry. A total of 100 adults with T2DM, who were normotensive and free from pre-existing cardiac conditions, were enrolled. Clinical details, glycaemic indices (FBS, PPBS, HbA1C), and echocardiographic measurements (via tissue Doppler imaging) were obtained and analyzed. LVDD was diagnosed based on established Doppler parameters. LVDD was identified in 91% of participants, with Grade I dysfunction being the most prevalent. Poor glycaemic control, longer disease duration, and elevated systolic/diastolic pressures were significantly associated with more advanced grades of dysfunction (p < 0.05). Diastolic dysfunction is highly prevalent in individuals with T2DM and shows a strong link with poor metabolic control. Routine cardiac evaluation in diabetic patients may facilitate early detection and timely intervention to reduce cardiac complications.